2022
DOI: 10.2147/cia.s356361
|View full text |Cite
|
Sign up to set email alerts
|

Higher Concentration of Adrenocorticotropic Hormone Predicts Post-Stroke Depression

Abstract: Background Post-stroke depression (PSD) is the most common neuropsychiatric complication after stroke, seriously affecting the quality of survivors’ life. As one of the important causes of PSD, neuroendocrine mechanism has been widely studied in recent years. The main objective of this study was to investigate the relationship between adrenocorticotropic hormone (ACTH) on admission and PSD at 3 months. Methods This is a hospital-based prospective cohort study, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that physical activity can effectively prevent or reduce the incidence of depression ( 5 , 39 ). In our study, physical activity was divided into two categories based on whether patients exercise moderately or vigorously every week, such as jogging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that physical activity can effectively prevent or reduce the incidence of depression ( 5 , 39 ). In our study, physical activity was divided into two categories based on whether patients exercise moderately or vigorously every week, such as jogging.…”
Section: Discussionmentioning
confidence: 99%
“…Post-stroke depression (PSD), as one of the most frequent psychiatric complications of cerebrovascular lesions, is closely linked to decreased functional status and higher mortality rates, which not only reduces the quality of life of patients but also places a heavy burden on caregivers ( 1 3 ). A new review reported that PSD prevalence was extremely high within 3 months after the acute event in the total stroke population ( 4 ), and our previously published literature showed that the overall prevalence of PSD at 3 months after stroke was up to 39.7% ( 5 ). Furthermore, a host of studies presented that there was a strong association between stroke severity and PSD ( 1 , 2 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that some associated sociodemographic factors differ in male and female PSD patients, such as age, cognitive impairment and physical exercise habits [ 14 , 15 ]. In addition, previous literatures have reported that some hormones were associated with PSD, such as free T3, free T4, thyroid stimulating hormone (TSH) [ 16 , 17 ], homocysteine [ 18 ], cortisol [ 19 ], brain derived neurotrophic factor (BDNF) [ 20 ], cortisol [ 21 ] and ACTH [ 22 ]. Only one study reported sex difference of blood biomarkers in PSD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…61,[99][100][101][102][103][104][105][106][107][108][109][110][111] Overall, evidence suggests that HPA axis dysfunction underpins a bidirectional relationship between many of these comorbidities and depression. 110,[112][113][114]…”
mentioning
confidence: 99%